Mitochondrial Acetylome Analysis in a Mouse Model of Alcohol-Induced Liver Injury Utilizing SIRT3 Knockout Mice - Fritz, Kristofer S. (2012)
Mitochondrial protein hyperacetylation is a known consequence of sustained ethanol consumption and has been proposed to play a role in the pathogenesis of alcoholic liver disease (ALD). The mechanisms underlying this altered acetylome, however, remain unknown. The mitochondrial deacetylase sirtuin 3 (SIRT3) is reported to be the major regulator of mitochondrial protein deacetylation and remains a central focus for studies on protein acetylation. To investigate the mechanisms underlying ethanol-induced mitochondrial acetylation, we employed a model for ALD in both wild-type (WT) and SIRT3 knockout (KO) mice using a proteomics and bioinformatics approach. Here, WT and SIRT3 KO groups were compared in a mouse model of chronic ethanol consumption, revealing pathways relevant to ALD, including lipid and fatty acid metabolism, antioxidant response, amino acid biosynthesis and the electron-transport chain, each displaying proteins with altered acetylation. Interestingly, protein hyperacetylation resulting from ethanol consumption and SIRT3 ablation suggests ethanol-induced hyperacetylation targets numerous biological processes within the mitochondria, the majority of which are known to be acetylated through SIRT3-dependent mechanisms. These findings reveal overall increases in 91 mitochondrial targets for protein acetylation, identifying numerous critical metabolic and antioxidant pathways associated with ALD, suggesting an important role for mitochondrial protein acetylation in the pathogenesis of ALD.